Cost-effectiveness of Balloon Kyphoplasty for Patients With Acute/Subacute Osteoporotic Vertebral Fractures in the Super-Aging Japanese Society. Issue 5 (1st March 2019) - Takahashi, Shinji; Hoshino, Masatoshi; Yasuda, Hiroyuki; Terai, Hidetomi; Hayashi, Kazunori; Tsujio, Tadao; Kono, Hiroshi; Suzuki, Akinobu; Tamai, Koji; Ohyama, Shoichiro; Toyoda, Hiromitsu; Dohzono, Sho; et al.
Abstract : Study Design: A propensity score matching study. Objective: The aim of this study was to assess the cost-effectiveness of balloon kyphoplasty (BKP) in Japan. Summary of Background Data: Osteoporotic vertebral fracture (OVF) is a common disease in elderly people. In Japan, the incidence of painful OVF in 2008 was estimated as 880, 000, and approximately 40% of patients with painful OVF are hospitalized due to the severity of pain. Japan is the front runner among super-aged societies and rising health care costs are an economic problem. Methods: BKP and nonsurgical management (NSM) for acute/subacute OVF were performed in 116 and 420 cases, respectively. Quality-adjusted life years (QALY) and incremental costs were calculated on the basis of a propensity score matching study. QALY was evaluated using the SF-6D questionnaire. Finally, using a Markov model, incremental cost-effectiveness ratios (ICERs) were calculated for 71 matched cases. Results: In the comparison between BKP and NSM, mean patients age was 78.3 and 77.7 years, respectively ( P  = 0.456). The BKP procedure cost 402, 988 JPY more than NSM and the gains in QALY at the 6-month follow-up were 0.153 and 0.120, respectively (difference = 0.033). ICERs for 3 and 20 years were 4, 404, 158 JPY and 2, 416, 406 JPY, respectively. According to sensitivity analysis, ICERs ranged from 652, 181 JPY to 4, 896, 645 JPY (4418–33, 168 GBP). Conclusion: This study demonstrated that BKP is a cost-effective treatment option for OVF in Japan. However, the effect might be blunted in patients aged > 80 years. Further research is necessary to elucidate the cost-effectiveness of BKP in this population. Level of Evidence: 4